2021
DOI: 10.1371/journal.pone.0260629
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in fish school spatial distribution and abundance under the Kuroshio regular pattern and the large meander in Suzu coastal waters

Abstract: The Kuroshio Current can take two paths; usually it follows the regular pattern but occasionally it follows a pattern known as the large meander. In this study, we investigated the abundance of fish that migrate to coastal waters and the spatial distribution of fish schools under both Kuroshio patterns in Suzu district, Kochi prefecture, where the set net is the main fishery industry. We clarified the seasonal variation in the density and distribution of fish schools using a quantitative echo sounder. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Another species, Seriola quinqueradiata (yellowtail), which is an oceanodromous species, undergoes a northward migration in its early life stages. This migration to recruit marine waters occurs from autumn to early winter [86]. Our study revealed a similar trend in which the yellowtail migrated to the shallow coastal shoreline as the water temperature declined during the autumn survey.…”
Section: Controlling Factors Of the Seasonal Fluctuations In Fish Com...supporting
confidence: 73%
“…Another species, Seriola quinqueradiata (yellowtail), which is an oceanodromous species, undergoes a northward migration in its early life stages. This migration to recruit marine waters occurs from autumn to early winter [86]. Our study revealed a similar trend in which the yellowtail migrated to the shallow coastal shoreline as the water temperature declined during the autumn survey.…”
Section: Controlling Factors Of the Seasonal Fluctuations In Fish Com...supporting
confidence: 73%
“…The upwelling induced by cold-core cyclonic eddies can significantly impact Japan's climate through coastal air-sea interactions (Sugimoto et al, 2020(Sugimoto et al, , 2021. It also influences biological production and local fisheries by re-stratifying the surface seawater through eddies (Kobari et al, 2020;Lizarbe Barreto et al, 2021;Zhu et al, 2021) and microscale turbulent mixing near the Kuroshio front (Nagai et al, 2015(Nagai et al, , 2017(Nagai et al, , 2019Uchiyama et al, 2017). Conversely, downwelling induced by warm-core anticyclonic eddies can suppress upper-ocean productivity (Uchiyama et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As of July 2023, this LM event has lasted for 6 years, which has become the longest ever recorded LM since a consistent observation by the Japan Meteorological Agency (JMA) started in the 1960s (Qiu & Chen, 2021). The ongoing LM has received much media attention in Japan, as it has been revealed to trigger extratropical cyclones with extreme rainfall (Hirata et al., 2019; Tochimoto & Iizuka, 2022), cause discomfort in summer over the greater Tokyo metropolitan area (Sugimoto et al., 2021), and modify the seasonal abundance and distribution of commercial fish (Chang et al., 2019; Zhu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%